The Effect of Motivation and Discipline on Employee Achievement at PT Abadi Lestari in Jakarta - Aden Prawiro Sudarso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of motivation and discipline on employee performance at PT. Abadi Lestari in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that motivation has a significant effect on employee performance by 39.9%, hypothesis testing is obtained t count > t table or (6.211 > 2.002). Discipline has a significant effect on employee performance by 35.9%, hypothesis testing is obtained t count > t table or (5.706 > 2.002). Motivation and discipline simultaneously have a significant effect on employee performance with the regression equation Y = 8.394 + 0.313X1 + 0.284X2 and the contribution of the influence is 51.5%, hypothesis testing is obtained by F arithmetic > F table or (30.228 > 2.770).